Liberal or lost? How political education and social media shape the ideological maze of students - Bolqiah, Luthfi Hasanal (Masyarakat, Kebudayaan dan Politik, 2025)
The ideological orientation and political attitudes of students are influenced by formal political education and exposure to social media; however, the interaction between these two factors in shaping ideological coherence, flexibility, and complexity remains underexplored. This study employs Patrick H. O’Neil’s theoretical framework to analyze the spectrum of political ideologies beyond the traditional left-right dichotomy. Using a descriptive comparative quantitative method, a survey involving 200 political science and non-political science students. The research reveals that political education does not always foster ideological consistency but rather enhances ideological diversity and flexibility. Political science students exhibit moderate ideological diversity, demonstrating openness to a broad spectrum of ideologies, including fascism and communism, particularly in discussions about corruption, the military, and political parties. However, this diversity does not correlate with a stronger inclination toward liberalism. In contrast, non-political science students display slightly higher ideological consistency, with a predominant leaning toward social democracy. While social media facilitates incidental exposure to political discourse, its role in driving ideological transformation appears limited. Furthermore, this study challenges the classic assumption that structured political education inherently promotes liberal attitudes, underscoring the need for an adaptive educational framework that accounts for the complexities of political engagement in the digital era.